MORE THAN JUST ENTERTAINMENT: "UPIN IPIN" ANIMATION OFFERS MALAYSIA'S INTERETHNIC MULTICULTURAL SPIRIT TO INDONESIAN AUDIENCES - Gede Pasek Putra Adnyana Yasa; I Nyoman Darma Putra; I B Gde Pujaastawa; I Nyoman Larry Julianto (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The animation "Upin Ipin" is a popular children's movie series in Indonesian audiences, including Denpasar, from 2010-2023. In the story, interethnic harmony and peace are reflected through the characters who play a role. This article analyzes how the animated series "Upin Ipin" represents the multicultural spirit in interethnic relations in Malaysia for Indonesian audiences. The effort to show interethnic harmony in Upin Ipin's animation is evident, although, in reality, multicultural problems still occur in society. This research uses a qualitative method; the data is studied using discourse analysis theory and ideology theory. The results show that Upin Ipin animation is one of the media that can be used as a means to shape, educate and neutralize issues related to ethnic stereotypes that exist in Malaysia. This article contributes to the understanding that Upin Ipin animation is not just entertainment but a medium to introduce multicultural life in Malaysia and encourage the spirit of interethnic multicultural.